(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This structured review synthesizes contemporary experimental and clinical evidence regarding the impact of chronic atmospheric air pollution on the postnatal development and morphogenesis of bronchus-associated lymphoid tissue (BALT). Electronic databases including PubMed, Scopus, and Web of Science were screened for peer-reviewed publications between 2000 and 2024. Evidence indicates that particulate matter (PM2.5, PM10), nitrogen oxides, sulfur dioxide, and urban airborne nanoparticles disrupt follicular organization, alter CD3+/CD20+ lymphocyte distribution, impair germinal center formation, and promote epithelial remodeling. Mechanistically, oxidative stress, cytokine imbalance (IL-6, TNF-α), and TGF-β-mediated tissue remodeling are central contributors. Early-life exposure appears to represent a critical window of immune vulnerability. The findings highlight the importance of morphological monitoring as an indicator of environmental immunotoxic risk.